Glucagon‐Like Peptide‐2 Alters Bile Acid Metabolism in Parenteral Nutrition–Associated Liver Disease. (28th July 2015) - Lim, David W.; Wales, Paul W.; Mi, Si; Yap, Jason Y. K.; Curtis, Jonathan M.; Mager, Diana R.; Mazurak, Vera C.; Wizzard, Pamela R.; Sigalet, David L.; Turner, Justine M.
Abstract : Background : We aim to study the mechanisms underlying our previous finding that exogenous glucagon‐like peptide‐2 (GLP‐2) treatment in a preclinical model of neonatal parenteral nutrition–associated liver disease (PNALD) improves cholestasis. Methods : Neonatal piglets received 17 days of parenteral nutrition (PN) therapy and either saline control (PN/Saline n = 8) or GLP‐2 treatment at 11 nmol/kg/d (PN/GLP‐2, n = 7). At terminal laparotomy, bile and liver samples were collected. The relative gene expression of enzymes involved in bile acid synthesis, regulation, and transport was measured in liver by reverse‐transcriptase quantitative polymerase chain reaction. Bile acid composition in bile was determined using tandem mass spectrometry. Data were analyzed using 1‐way analysis of variance (ANOVA) or Kruskal‐Wallis ANOVA. Results : GLP‐2 increased the expression of bile acid export genes: multidrug resistance–associated proteins 2 (MRP2) ( P = .002) and 3 (MRP3) ( P = .037) over saline control. GLP‐2 increased expression of Farnesoid X receptor (FXR) ( P < .001) and CYP7A1 (cytochrome P450, family 7, subfamily A, polypeptide 1) ( P = .03). GLP‐2 treatment was associated with decreased concentrations of taurohyocholic acid and conjugates of toxic lithocholic acid ( P < .01). GLP‐2 treatment increased the liver bile acid content. Conclusions : GLP‐2 treatment was associated with alterations in the hepatic expression of genes involved in bile acid metabolism. The transcriptomic results indicate the mechanisms at the transcriptional level acting to regulate bile acid synthesis and increase bile acid export. Differences in bile acid profiles further support a beneficial role for GLP‐2 therapy in PNALD.